Cations and anions uptake by coastcross grass fertilized with urea and ammonium nitrate - Primavesi, Ana Cândida; Primavesi, Odo; Corrêa, Luciano Almeida; Cantarella, Heitor; Silva, Aliomar Gabriel da (Pesquisa Agropecuaria Brasileira, 2005)
Physiologic processes of plants are affected by uptake of cations and anions. The aim of this work was to determine the uptake of cations and anions when plants of coastcross grass received high doses of nitrogen. The experimental design was a randomized block, in a 2x5 factorial arrangement – two N sources: urea and ammonium nitrate and five N rates: 0, 25, 50, 100, and 200 kg ha-1 cutting-1 – with four replications. Treatments were applied after each of five consecutive cutting in the rainy season. Uptake of cations and anions by coastcross grass increased with increasing of N rates with both fertilizers, but was higher with ammonium nitrate. Increasing rates of N caused higher K+ uptake in relation to other cations, and in Cl- among the anions. Except for N, K+ uptake was greater than that of other nutrients, with a reduction on the relative content of Ca2+. High doses of N as urea or ammonium nitrate applied on coastcross grass favor absorption of cations and anions.